2011
DOI: 10.1016/j.solener.2011.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Performance model for parabolic trough solar thermal power plants with thermal storage: Comparison to operating plant data

Abstract: This paper describes a simulation model that reproduces the performance of parabolic trough solar thermal power plants with a thermal storage system. The aim of this model is to facilitate the prediction of the electricity output of these plants during the various stages of their planning, design, construction and operation. Model results for a 50 MWe power plant are presented and compared to real data from an equivalent power plant currently operated by the ACS Industrial Group in Spain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(40 citation statements)
references
References 14 publications
0
38
0
2
Order By: Relevance
“…Figure 3 shows a schematic representation of the disposition of the TES in a solar thermal plant. This type of representations is widely accepted in literature [2,28,42] to represent the three main circuits in plants of this kind: the solar field (SF), through which the heat transfer fluid (HTF) circulates, the power block, which circulates water and steam, and the TES system. The performance of a TES system defines three possible operation modes: charge, discharge and idle mode.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 3 shows a schematic representation of the disposition of the TES in a solar thermal plant. This type of representations is widely accepted in literature [2,28,42] to represent the three main circuits in plants of this kind: the solar field (SF), through which the heat transfer fluid (HTF) circulates, the power block, which circulates water and steam, and the TES system. The performance of a TES system defines three possible operation modes: charge, discharge and idle mode.…”
Section: Methodsmentioning
confidence: 99%
“…Several numerical models for parabolic trough CSP plant that include thermal storage system have been developed by different organizations [160][161][162][163][164]. All these models only consider the conventional molten-salt two-tank storage system for which outlet/inlet temperatures are fixed.…”
Section: Integration and Seamless Operation Of Csp Using Thermocline mentioning
confidence: 99%
“…Numerous researchers have addressed various issues and tackled with numerous aspects of solar power production [1][2][3][4][5][6][7][8]. Experimental and theoretical studies carried out by several researchers have shown that solar photovoltaic or photovoltaic thermal technologies are best suited for independent power and heat production.…”
Section: Introductionmentioning
confidence: 99%